Sistemas microemulsionados visando à remoção de depósitos parafínicos - Aum, Yanne Katiussy Pereira Gurgel (2016)
Paraffin deposition is a critical issue in the petroleum industry, since it can crucially affect both transport and production operations. In spite of the diversity of remediation techniques, those currently used may present problems and limitations when applied, due to the great number of different scenarios that can be found. Even though the microemulsions display a high potential for solubilization, the studies related to their application in paraffin removal are very scarce. Thus, this work aimed to develop oil-in-water (O/W) microemulsion systems (ME) with high capacity of removing paraffin deposits. Several formulations of four different O/W microemulsion systems were evaluated. The aforementioned systems were composed by: ALK-L90 as surfactant; butan-1-ol as cosurfactant; distilled water; and as oil phase, four different components (kerosene, xylene, diesel and a kerosene-xylene mixture). The systems were characterized regarding phase equilibrium, particle size, surface tension and rheology. Paraffin surface wettability studies related to these systems, as well as studies on the rheological behaviour of each of the ME systems containing paraffin, under different temperatures, were performed aiming to assess the fluid-paraffin interaction. A methodology to evaluate the efficiency of paraffin removal in pipelines was developed and applied for the performance evaluation of each of the proposed systems. The results demonstrated that the chemicals used favoured the formation of Winsor-IV O/W microemulsions. The wettability studies confirmed the high interaction capacity between the ME systems and the paraffin surface. Also, the ME systems with paraffin presented Binghamian and Newtonian behaviors, with a great pumping capacity due to the low values of viscosity and initial flow tension. The removal efficiencies of the O/W ME systems were similar to and, in some cases, even higher than the efficiencies of pure solvents, despite the high water percentage. The statistical analysis and modelling of the experimental data generated models there are able to both describe and estimate the removal efficiency as a function of the ME system composition, as well as to understand its action mechanism. Therefore, the proposed O/W ME systems present a valid alternative in the removal of paraffin deposits, with lower environmental risks and inflammability than the conventional systems used in the industry.